Investigations on the Hemostatic Potential of Physiological Body Fluids - Thaler, Johannes; Tripisciano, Carla; Nieuwland, Rienk (Hämostaseologie, 2024)
Current blood coagulation models consider the interactions between blood, the vessel wall, and other tissues that expose tissue factor (TF), the main initiator of coagulation. A potential role of body fluids other than blood is generally not considered. In this review, we summarize the evidence that body fluids such as mother's milk saliva, urine, semen, and amniotic fluid trigger coagulation. The ability of these body fluids to trigger coagulation is explained by the presence of extracellular vesicles (EVs). These EVs expose extrinsic tenase complexes (i.e., complexes of TF and activated factor VII) that can trigger coagulation. Why these body fluids share this activity, however, is unknown. Possible explanations are that these body fluids contribute to hemostatic protection and/or to the regulation of the epithelial barrier function. Further investigations may help understand the underlying cellular and biochemical pathways regulating or contributing to coagulation and innate immunity, which may be directly relevant to medical conditions such as gastrointestinal bleeding and chronic inflammatory bowel disease.
Keywords: tissue factor; factor VIIa; extracellular vesicles; physiological body fluids